Efficacy of single spray of fungicides on early leaf spot (Cercospora arachidicola) of groundnut (Arachis hjpogaea)* - CHANDRA, SATISH; SINGH, A K; BAISWAR, PANKAJ (The Indian Journal of Agricultural Sciences, 2011)
An experiment war conducted during 2004 and 2005 to manage the early leaf spot disease by minimum application of fungicides and plant-based chemicals. Out of eight fungicides tested at Barapani, Meghalaya against early leaf spot of groundnut, maximum control was shclwn by Diathane M-45+ Bavistin (40.2%) , Saaf (39.1%) with a cost benefit ratio of 1 :2.85 and 1:2.67. It is evident from the findings that early leaf spot can be effectively and economically managed by using short duration variety and timely planned single spray of either Dithane M45 + Bavistin or Saaf under rainfed condition in hills where late leaf spot and rust are not major problems.